Professores com distúrbios vocais: efeitos do método de ressonância Lessac-Madsen - Oliveira, Luciana Vieira Dias Alves de (2007)
Introduction: Lessac-Madsen Resonance Method for vocal therapy is a resonant voice-based training. This voice involves a healthy production with the vocal folds lightly abducted and it propitiates a strong, clear production with minimum effort. Objective: to check the pre and post effects of the program based on Lessac-Madsen Resonance Method in teachers that show vocal disturbances. Methods: The study was carried out at a Public Hospital of the city of São Paulo with 17 teachers with medical diagnosis of nodules in vocal folds, divided in two groups: Experimental-EG and control-CG (10 and 7, respectively). The ten EG participants were cared individually, in a total of eight sessions, once a week, following the Lessac Madsen Resonance Method program. All teachers (EG and CG) were submitted to two evaluations, initial and final: Protocol for checking the vocal symptoms and voice changes along the class, score attributed by the teachers as for their voice, voice recording, videolaryngoscopy and protocol to check the benefits of the method according with the own teachers' perception, whereas that last one was just accomplished by the EG. Voice recordings were submitted to the perceptive-hearing evaluation through chained and spontaneous speech and acoustic analysis by using the vowels /a/ and /i/. Results: In the final evaluation, the EG showed a statistically significant reduction in all the vocal symptoms and significant increase in the scores as for the global voice deviation, when compared with the initial evaluation (4.70%) and final evaluation (8.50%). The perceptive-hearing evaluation pointed out improvement in vocal quality, resonance, pitch, loudness and vocal attack. The acoustic analysis measurements indicated statistically significant reduction in irregularity, shimmer and jitter parameters, and the values of f0 and PHR were higher, however, with no statistical significance in those results. In the otorhinolaryngological diagnosis through videolaryngoscopy, a significant reduction in the nodular lesion was verified in 50% of the sample. As for the post-method vocal benefits, 70% of the teachers revealed plenty reduction in the vocal symptoms, clearer voice, followed by easy speech. From the sample, 50% revealed much more easiness in strong speech and 70% declared plenty dedication to the treatment. Use of resonant voice in other communicative contexts was reported by the teachers (50%) as plenty. The whole sample (100%) revealed that the method was very interesting. In the CG there was no improvement in the appraised parameters. Conclusion: The results allowed to check Lessac Madsen Resonance Method s benefits in reducing vocal symptoms, vocal quality improvements, reduction of nodular lesion and it enabled the teacher to use the clearest voice, in an easy way and effortlessly along the class